ANALISIS PENGARUH PERPUTARAN PERSEDIAAN DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PERUSAHAAN OTOMOTIF DI BEI - Jonathan Silaban, Chandro; Siregar, Lukman Hakim; Anan, Malesa (Jurnal Manajemen Akuntansi dan Ilmu Ekonomi, 2025)
This study aims to analyse the effect of inventory turnover and sales growth on profitability in automotive sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. Data obtained from the financial statements of ten companies in the automotive sub-sector for five years. The research method used is descriptive quantitative with a multiple linear regression statistical approach to test the effect of independent variables (inventory turnover and sales growth) on the dependent variable (profitability measured by Return on Assets / ROA). The results showed that partially, inventory turnover and sales growth do not always have a significant effect on profitability, but simultaneously both have a contribution to the company's profitability. These findings can provide input for company management in managing inventory and sales strategies to improve financial performance, as well as a reference for further research in the field of accounting and financial management of automotive companies in Indonesia.